Encyclopedia of sociology - Borgatta, Edgar F.; Montgomery, Rhonda (Macmillan Reference USA, 2000)
Presents nearly four hundred entries in which various scholars explore concepts and themes in sociology, arranged alphabetically over five volumes from adolescence to world religions; and includes a comprehensive index.